The Relationship Between Maternal Nutritional Intake Patterns and the Incidence of Anemia Among Third-Trimester Pregnant Women at Majalaya Public Health Center Bandung Regency - Rahayu, Indah; Ghasyiyah, Virna (Rifa'Institute, 2026)
Introduction: The Indonesian Health Survey (SKI) 2023 reported a decrease in anemia prevalence among pregnant women from 48.9% to 27.7%. However, local data at Majalaya Public Health Center showed an increase from 15 cases (1.04%) in 2022 to 46 cases (3.35%) in 2023. A balanced nutritional intake plays a key role in preventing anemia during pregnancy. Objective: This study aimed to determine the relationship between nutritional intake patterns and the incidence of anemia among third-trimester pregnant women at Majalaya Public Health Center, Bandung Regency. Method: This was a correlational study using a cross-sectional design, conducted from January to July 2025. The population consisted of 98 third-trimester pregnant women, with data collected through primary sources. Data analysis was performed using the Chi-square test with a significance level of p ≤ 0.05. Result and Discussion: Statistical analysis showed a significant relationship between nutritional intake patterns and anemia incidence, with a p-value of 0.002 (< α = 0.05), indicating that inadequate nutrition is associated with a higher risk of anemia. Conclusion: Nutritional intake patterns have a significant association with the incidence of anemia in third-trimester pregnant women at Majalaya Public Health Center.